2020
DOI: 10.1108/ijchm-07-2019-0621
|View full text |Cite
|
Sign up to set email alerts
|

Gendered and diversified? Leadership in global hospitality and tourism academia

Abstract: Purpose This paper aims to represent a unique and original piece of research on full professors in global hospitality and tourism academia. Aimed at revisiting academic leadership, this study identifies its components and gains insight into the so far understudied dimensions of diversity in academic contexts worldwide. Design/methodology/approach Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Additionally, job motivation was explored using LGCM to detect its change trajectories. We also partialed out the effect of gender on our study variables by controlling for this demographic variable (Gewinner, 2020). It is shown that the effects of gender on the study variables are not significant, with the standardized coefficients ranging from −0.05 to 0.08 ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, job motivation was explored using LGCM to detect its change trajectories. We also partialed out the effect of gender on our study variables by controlling for this demographic variable (Gewinner, 2020). It is shown that the effects of gender on the study variables are not significant, with the standardized coefficients ranging from −0.05 to 0.08 ( p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…This is a huge limitation considering the powerful effects that inclusion (Luu, 2022) and equity (Im et al , 2023) have on hospitality firms. Both surface-level (Gewinner, 2020) and deep-level (Yang et al , 2022) diversity may be accounted for through an inclusion lens and wider theoretical foundation provided by LIT. LIT could also extend hospitality DM research by proffering additional outcomes to be explored that DM alone was previously incapable of explaining, such as organizational trust, employee well-being and organizational citizenship.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…In the last paper titled “Gendered and diversified? Leadership in global hospitality and tourism academia,” Gewinner (2020) focused on diversity in academic leadership. The sample consisted of Full professors in the UK, the USA, German-speaking countries (Germany, Austria and Switzerland) and the Asia-Pacific region (Australia, New Zealand, China, Malaysia, Singapore and South Korea).…”
Section: The Papers In This Special Issuementioning
confidence: 99%